The Southern Center for Maternal Health Equity (SCMHE): a multisector multifaceted community-based approach to reduce disparities in maternal morbidity and mortality in the Gulf South - Melissa Goldin Evans; Maeve Wallace; Alessandra N. Bazzano; Joseph R. Biggio; Kiara Cruz; Abigail Gamble; Carmen Green; Zainab Jah; Sherri Longo; Susan Perez; Rachael N. Reed; Jeffrey G. Shaffer; et al. (Frontiers in Public Health)
IntroductionThe maternal mortality crisis in the United States disproportionately affects women who are Black, especially those living in the Gulf South. These disparities result from a confluence of healthcare, policy, and social factors that systematically place Black women at greater risk of maternal morbidities and mortality. This study protocol describes the Southern Center for Maternal Health Equity (SCMHE), a research center funded by the National Institutes of Health in 2023 to reduce preventable causes of maternal morbidity and mortality while improving health equity. This is a seven year program with pilot and implementation phases. SCMHE is co-led by three organizations: Reproductive Health Impact (a fiscally sponsored project of the Praxis Project), an advocacy community-based organization; Tulane University, an academic research institute; and Ochsner Health, a large regional nonprofit health system.MethodsSCMHE applies a multilevel life course approach based on the Social Ecological Model to prevent maternal morbidity and mortality with interventions at individual, interpersonal, institutional, community, and societal levels. This community-focused research center uses an intersectional lens and the Reproductive Justice framework in its aims to improve maternal health and strengthen community-based maternal health research capacity in Louisiana and Mississippi.DiscussionTo advance the field of maternal health using participatory, community-centered, and radically equity-focused approaches previously underutilized and under-evaluated, the Center will lead three R01 projects to assess the implementation of existing evidence-based strategies and build the evidence base for translational research strategies.Ethics and disseminationBy leveraging our team's existing network with local, regional, and national partners while continuing to build new, unique interdisciplinary partnerships, we will build upon our distinctive interdisciplinary strengths and community connections to bring our outreach and technical assistance efforts to diverse audiences.